Dental caries and sugar intake of children from rural areas with different water fluoride levels in Paraı´ba, Brazil - Sampaio FC, Nazmul Hossain ANM, von der Fehr FR, Arneberg P (Blackwell Synergy, 2000)
Few reports have investigated caries prevalence in rural areas of Brazil. Objective: The aim of this study was to observe the caries prevalence (DMFT, DMFS) in 12-year-old children living in rural villages of Paraı´ba, Brazil with low and moderate fluoride levels in the drinking water and to relate it to sugar intake and oral hygiene. Methods: One hundred and ninety four children from 13 villages were grouped according to the water fluoride levels: low fluoride (LF, ,0.2 ppm F, 96 children) and moderate fluoride (MF, 0.7–1.0 ppm F, 98 children). Caries and oral hygiene (OHI-S) were scored according to WHO criteria. Sugar intake was assessed through interviews.